Communicating the spatiotemporal transformation of architectural heritage via an in-situ projection mapping installation. (December 2018) - Nofal, Eslam; Stevens, Robin; Coomans, Thomas; Vande Moere, Andrew
Abstract: Understanding the spatial transformation of architectural heritage over time is crucial for documentation and conservation purposes, but also for communicating the salient architectural features of the buildings' evolution to the public at large. With the rapid evolution of physical computing technologies such as electronics, sensors and digital projections, we believe that the technique of projection mapping offers great potential in communicating heritage in-situ because its graphical depiction on the heritage itself can more directly relate to the real context in more experiential ways. Furthermore, digital projections can include various interactive functionalities that together with its architectural size provide an immersive experience that is dynamic and adaptable to the interests of the visitors. Consequently, this paper aims to investigate the deployment of an interactive projection mapping installation in-situ which can be steered by a tangible user interface (TUI). Through an in-the-wild study, we deployed a mixed-method evaluation to investigate how such an interactive projection mapping enhances the communication of the spatiotemporal transformation of a medieval chapel that occurred during the last 850 years. Our findings show how the in-situ projection positively affects visitors' understanding and memorability of the aesthetic features, and how its combination with a tangible interface enhances the communication of the spatial features of the chapel over time, and allows for more social interaction among them. The paper concludes with several discussion points and recommendations for applying interactive projection mapping and TUIs in the context of architectural heritage.